Desalinización de agua: ¿una alternativa sostenible para la potabilización del agua? (2018)
In this project, a theoretical investigation was made about the techniques that have been developed worldwide for the use and consumption of water from the desalination of seawater or brackish water, the advantages and disadvantages of the application of technologies, and the future of this process as a sustainable alternative for the purification of water. Throughout history, the purification of the seawater resource has presented several disadvantages due to the costs associated with infrastructure, energy consumption, environmental consequences, salinity limitations for human consumption and research to improve the process.